Hydrophilic, dual amino acid–functionalized zinc sulfide quantum dot for specific identification of N‐glycopeptides from biological samples - Feng, Quanshou; Xie, Zehu; Liang, Hongze; Zhang, Zhenbin; Yan, Yinghua; Ding, Chuan‐Fan (Rapid communications in mass spectrometry, 2022)
Rationale Glycosylation of proteins is one of the most significant and complex post‐translational modifications, and N‐glycosylation plays a crucial role in life activities. Mass spectrometry (MS) has been a powerful technique in the analysis of protein glycosylation. However, the direct detection of glycoproteins in biological samples based on MS still suffers from huge challenges. Therefore, enrichment and purification of samples before MS analysis is an essential prerequisite. Methods Hydrophilic interaction liquid chromatography (HILIC) has significantly developed for selective enrichment of glycopeptides due to its simple operation process and unbiased enrichment. Herein, hydrophilic, dual amino acid–functionalized zinc sulfide quantum dots (ZnS QDs) were prepared to enrich glycopeptides using an easy procedure. The enriched glycopeptides were detected using matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS). Results The obtained material exhibited high selectivity (1:2000), low detection limit (0.1 fmol/μl), good repeatability (10 times), and excellent recovery (89.8%) in glycopeptide enrichment. In the actual application in biological samples, 71 N‐glycopeptides and 161 N‐glycopeptides were detected from human saliva and serum, respectively. Conclusions ZnS‐Au‐GC was successfully prepared using an easy method. The results showed that the obtained material exhibited excellent performance in glycopeptide enrichment. Furthermore, it had showed great potential for glycopeptide enrichment in complex biological samples.